2021
DOI: 10.1371/journal.pone.0240642
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal HMB supplementation on bone mechanical and geometrical properties, as well as histomorphometry and immunolocalization of VEGF, TIMP2, MMP13, BMP2 in the bone and cartilage tissue of the humerus of their newborn piglets

Abstract: The presented experiment focuses on assessing the impact of HMB (hydroxy-β-methobutyrate) supplementation of mothers during pregnancy on the development of the skeletal system of their offspring. For this purpose, an experiment was carried out on 12 clinically healthy sows of the Great White Poland breed, which were divided randomly into two groups the control and the HMB group. All animals were kept under standard conditions and received the same feed for pregnant females. In contrast, females from the HMB gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Negative control sections for each antibody were conducted by identical immunohistochemical staining excluding the primary antibody ( Supplementary Data, Figure S1 ). The intensity of immunoreaction was measured using a CX43 microscope (Olympus, Tokyo, Japan), both by determining the percentage of cells with a positive response, and by the quantitative comparison of mean pixel intensity in the photomicrographs, which were firstly converted into negatives and then into 8-bit grey-scale digital images, with a scale from 0 (white pixel) to 255 (black pixel), where the higher the pixel value, the higher the intensity of the immunohistochemical reaction [ 29 , 44 ]. For the immunoreactive cell count procedure, four randomly selected areas of compact bone, trabecular bone and articular cartilage, respectively, were measured for each microscopic slide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative control sections for each antibody were conducted by identical immunohistochemical staining excluding the primary antibody ( Supplementary Data, Figure S1 ). The intensity of immunoreaction was measured using a CX43 microscope (Olympus, Tokyo, Japan), both by determining the percentage of cells with a positive response, and by the quantitative comparison of mean pixel intensity in the photomicrographs, which were firstly converted into negatives and then into 8-bit grey-scale digital images, with a scale from 0 (white pixel) to 255 (black pixel), where the higher the pixel value, the higher the intensity of the immunohistochemical reaction [ 29 , 44 ]. For the immunoreactive cell count procedure, four randomly selected areas of compact bone, trabecular bone and articular cartilage, respectively, were measured for each microscopic slide.…”
Section: Methodsmentioning
confidence: 99%
“…Functional food or supplements affecting skeletal tissue remodeling and homeostasis can be useful for prevention before PLO. Based on previous results, HMB supplementation during pregnancy has been shown to have a positive effect, not only on the offspring, but also on the pregnant dam’s skeletal system [ 21 , 27 , 28 , 29 ]. Taking into account the influence of pregnancy on bone quality and the effect of HMB in protecting pregnant women against excessive bone loss, it seems reasonable to investigate the effects of HMB supplementation during pregnancy on the immunolocalization of selected proteins involved in bone metabolism in pregnancy and lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on pigs supplemented with HMB have shown that it regulates lipid metabolism, promoting fat oxidation, which could potentially improve body composition and aid in fat loss [22][23][24]. Additionally, HMB enhanced piglets bone health by promoting bone formation, reducing resorption, and increasing bone density [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, irrespective of their MMP neutralizing actions, TIMPs are thought to have implications of pluripotency on cellular functions, such as cell proliferation, movement, endurance, and differentiation [ 13 ]. Tissue inhibitor of metalloproteinases 2 (TIMP-2) expression is lower in studies with pregnant pig mothers receiving hydroxy—methobutyrate supplementation for the skeletal development of their piglets, which could imply that these supporting tissues of animals are undergoing greater remodeling [ 14 ]. The effect of a combination of anabolic growth factors and a protease inhibitor on an in vitro culture of articular chondrocytes revealed that TIMP-2 was beneficial in enhancing ECM synthesis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%